RESPON TERHADAP MAJELIS AGAMA BUDDHA TENTRAYANA SATYA BUDDHA INDONESIA DI KALIMANTAN BARAT (Harmoni, 2012)
There are many sects of  Buddhism , some  of them are Theravada or Hinayana, Satya Buddhism and Tantrayana Zhenfo Zhong. The last one, is developed by Lu Sheng in Seattle, USA. The difference of this school with other Buddhism teachings is the life of Buddha, teacher`s cult, Bhiksu and  Bhiksuni can marry and glamorious life of  its tearcher. The live Buddha is known with his teachings that people are  enlightened and still life. Those followers of Tantrayana which is known as live Buddha is Lu Sheng Yen himself as Maha Mula Vajra Acharya.  This research is done by qualitative approach.
Keywords: Sekte; Buddha hidup; Tantrayana; Buddha; sect; live Buddha; Buddhism